ABANGAN, SANTRI, PRIYAYI: ISLAM DAN POLITIK IDENTITAS KEBUDAYAAN JAWA - Zubair Zubair (DIALEKTIKA, 2018)
Javanese culture and Islam are the two entities that are difficult to be separated. Both meet and create co-existence singkretik so that discussion of Javanese culture can hardly be separated from Islam, including in the political field. The works on Islamic Java continue to emerge, especially in the sociological-anthropological perspective. Since Geertz conduct a study on The Religion of Java, the study continues, either agree with him or who reject it. This paper intentionally taking the starting point of Geertz’s Studieswith concept of trikhotomi. Regardless of excess or weakness Geertz's conception, but it should be underlined that Geertz conception about the Islamic Java much a source of inspiration for the study of Javanese culture and even Indonesia. Even in its development, the conception was brought into the political arena into identity politics. Identity politics is political action to promote the interests of the members of a group have a similar identity or characteristics, whether based on race, ethnicity, gender, or religion. Identity politics is another formulation of political differences. The emergence of identity politics is a response to the implementation of human rights are often applied unfairly